Party, ethnicity, or region? Determinants of informal political exchange in the parliament of Ghana. (July 2018) - Osei, Anja; Malang, Thomas
This article analyzes the patterns of informal political exchange between Ghanaian parliamentarians. Whereas research on Western parliaments identifies the party dimension as the strongest predictor for explaining exchange patterns, we develop three possible theoretical explanations for non-Western legislatures. We try to explain informal political exchange by shared ideology (party), solidarity (ethnicity), or same material interests (region). We test our claims by a novel data set based on a survey with almost all members of the current Ghanaian legislature. We analyze the exchange network using exponential random graph models. Our results suggest that regional origin, as compared to party attachment and ethnicity, is the superior predictor for informal political exchange between parliamentarians.